2021
DOI: 10.1038/s41598-021-87858-9
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium nitrite as a corrosion inhibitor of copper in simulated cooling water

Abstract: The corrosion inhibition behavior of sodium nitrite (NaNO2) towards pure copper (99.95%) in simulated cooling water (SCW) was investigated by means of electrochemical impedance spectroscopy (EIS) and dynamic electrochemical impedance spectroscopy (DEIS). NaNO2 interferes with metal dissolution and reduce the corrosion rate through the formation or maintenance of inhibitive film on the metal surface. Surface morphologies illustrated that the surface homogeneity increased on adding sodium nitrite. Sodium nitrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…This one was confirmed in this investigation, which revealed that the equilibrium constant was significantly higher than in earlier studies. 100,101 Langmuir isotherms were found to provide a better explanation for the adsorption method of Eruca sativa seed extract on the carbon steel surface than Henry due to the precision of R 2 . The Gibbs free energy adsorption values are intended using eqn (17). K ads = 1/55.5 exp(Δ G 0 ads / RT )…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…This one was confirmed in this investigation, which revealed that the equilibrium constant was significantly higher than in earlier studies. 100,101 Langmuir isotherms were found to provide a better explanation for the adsorption method of Eruca sativa seed extract on the carbon steel surface than Henry due to the precision of R 2 . The Gibbs free energy adsorption values are intended using eqn (17). K ads = 1/55.5 exp(Δ G 0 ads / RT )…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Belirlenen frekans aralığına bağlı olarak bir sistemin empedansını ölçmek için kullanılan bir elektrokimyasal tekniktir [15]. Sistem ara yüzünde meydana gelen elektrokimyasal etkileşim uygun devre modeli aracılığıyla simule edip hesaplanmaktadır [16]. İncelenen sistem ara yüzünde meydana gelen elektrokimyasal süreçlerin fiziksel temsili olan pasif elektrik bileşenleri (yani dirençler R, kapasitörler C ve endüktanslar L) hesaplanabilmektedir.…”
Section: ) Elektrokimyasal Empedans Spektroskopisi (Eis)unclassified
“…Currently, various corrosion inhibitors, which are divided into organic and inorganic corrosion inhibitors, have been investigated globally [1b,5] . Inorganic corrosion inhibitors are classified into four types based on their extensive use, diversity, and ability to complete current processes: nitrite corrosion inhibitors, [6] chromate corrosion inhibitors, [7] molybdenum salts, [8] and tungstate corrosion inhibitors [9] . Organic corrosion inhibitors with green environmental protection, less dosage, and mature research, are mainly divided as azole compounds, [10] amines, [11] amino acids, [12] triphenylmethane derivatives, sulfhydryl compounds, phosphates, and other organic compounds [13] .…”
Section: Introductionmentioning
confidence: 99%